Transcriptome-Wide Identification and Characterization of MYB Transcription Factor Genes in the Laticifer Cells of Hevea brasiliensis - Wang, Ying; Zhan, Di-Feng; Li, Hui-Liang; Guo, Dong; Zhu, Jia-Hong; Peng, Shi-Qing (Frontiers in Plant Science, 2017)
MYB transcription factors hold vital roles in the regulation of plant secondary metabolic pathways. Laticifers in rubber trees (Hevea brasiliensis) are of primary importance in natural rubber production because natural rubber is formed and stored within these structures. To understand the role of MYB transcription factors in the specialized cells, we identified 44 MYB genes (named HblMYB1 to HblMYB44) by using our previously obtained transcriptome database of rubber tree laticifer cells and the public rubber tree genome database. Expression profiles showed that 5 MYB genes were highly expressed in the laticifers. HblMYB19 and HblMYB44 were selected for further study. HblMYB19 and HblMYB44 bound the promoters of HbFDPS1, HbSRPP, and HRT1 in yeast. Furthermore, the transient overexpression of HblMYB19 and HblMYB44 in tobacco plants significantly increased the activity of the promoters of HbFDPS1, HbSRPP, and HRT1. Basing on this information, we proposed that HblMYB19 and HblMYB44 are the regulators of HbFDPS1, HbSRPP, and HRT1, which are involved in the biosynthesis pathway of natural rubber.